SBA-15 intercalated Mg-Al hydrotalcite: an environmental friendly catalyst for hydroisomerization of olefin - Baskaran, Thangaraj; Christopher, Jayaraj; Ajithkumar, Thalasseril G.; Sakthivel, Ayyamperumal (Applied Catalysis A-General, 2014)
SBA-15 Molecular sieve-intercalated Mg-Al hydrotalcite (MASBA-HT) was synthesized for the first time by a simple straightforward method. The intercalation of SBA-15 molecular sieve between the interlayer of HT was evident from powder XRD, TEM and FT-IR studies. The presence of SBA-15 facilitates retention of the layered structure for first time, even after calcination at high temperature of 550 degrees C. The resultant material possesses moderate acidity which comes from incorporation of aluminum into the framework of SBA-15 and also contained soluble basicity similar to HT materials. The material shows promising activity for hydroisomerization of 1-octene resulting in good substrate conversion (80%) and branched isomers selectivity (45%). The catalytic activity remains constant over longer duration and repeated runs. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Branched alkenes; Hydroisomerization; Intercalated-hydrotalcite; layered materials; Mesoporous SBA-15